Learning Assistance as a Solution to Improve Literacy and Numeracy Skills for Primary School Students - Sapanora, Anjeli; Juselda, Juselda; Sikumbang, Laila Husna; Febriyani, Rika; Ie, Mei (Journal of Innovation and Community Engagement, 2025)
Many students face challenges in mastering reading, writing, and arithmetic due to the limitations of preschool education, low learning support from families, and the lack of available learning resources. In addition to the above reasons, it cannot be denied that the lack of interest and motivation to learn is also one of the reasons why many students have not been able to master these basic numeracy and literacy skills. Therefore, this community service activity aims to improve basic reading, writing, and counting skills in students from grade 1 to 3 of SDN X Ciherang. This mentoring programme is designed as a form of preparation for the calistung competition through a fun learning approach and focuses on improving basic academic skills. The methods used in this activity are quantitative and qualitative methods, through the implementation of pre-test and post-test that have met the standards of the Ministry of Culture, Research and Technology, observation of student learning behaviour, and short interviews. Mentoring activities were carried out for approximately three weeks with a frequency of 2-3 times per week. The evaluation results showed a significant improvement in students' abilities in reading, writing, and counting after being given intensive guidance. In addition to improving academic skills, students also showed a more positive attitude towards learning. This activity shows that tutoring designed according to the needs of children and the local context can improve students' readiness to participate in competitions, as well as have a positive impact on their motivation and confidence in learning.